Language Abilities and Peer Rejection in Kindergarten: A Mediation Analysis. Issue 2 (17th February 2020) - van der Wilt, Femke; van der Veen, Chiel; van Kruistum, Claudia; van Oers, Bert
ABSTRACT: Rejection by peers has devastating effects on children's social-cognitive development. As language difficulties have been found to be one of the underlying causes of peer rejection, the present study focused on the relation between these two variables. Specifically, this study was the first to test a hypothesized model connecting children's level of receptive vocabulary knowledge to the extent to which they are rejected by their peers, through their ability to communicate effectively. A sample of N = 135 children (aged four to six) participated in the study. Their receptive vocabulary knowledge was assessed with the Peabody Picture Vocabulary Test, the level of oral communicative competence was measured using the Nijmegen Test for Pragmatics, and peer rejection was indicated by means of a nomination procedure. Research Findings : Outcomes of mediation analyses revealed that children's receptive vocabulary knowledge was indirectly related to peer rejection, through oral communicative competence: Poor receptive vocabulary knowledge was associated with poor oral communicative competence, which was in turn related to a higher level of peer rejection. Gender was not a significant moderator in this model. Practice or Policy : Findings suggest the need to focus both on oral communicative competence and on receptive vocabulary knowledge when addressing peer rejection in kindergarten.